Both-sided native valve endocarditis in an intravenous drug misuser. (11th December 2013) - Oylumlu, Muhammed; Ercan, Suleyman; Basanalan, Fuat; Davutoglu, Vedat
Abstract : Infective endocarditis (IE) is more common in left heart chambers in the general population. Right-sided IE is increased especially in intravenous drug misusers. However, involvement of both right and left heart chambers is extremely rare in these patients. In this study, we present the case of a 26-year-old male intravenous drug misuser, hospitalised with Staphylococcal tricuspid valve IE complicated with pulmonary septic embolism. After 10 days, an echocardiogram revealed vegetation on the mitral valve in addition to unchanged tricuspid valve vegetation. IE can be a rapidly progressive disease despite the medical treatment in intravenous drug misusers. Generally, the right-sided IE is common in intravenous drug misusers; however, as in our case, it may involve left heart chambers as well. Therefore, in the right-sided IE cases, a serial echocardiographic examination of both heart chambers is strictly recommended.